The formation of student character education during distance learning - Salira Syahwi Istiqomah (ETUDE: Journal of Educational Research, 2021)
Background: The COVID-19 pandemic is very bad for all areas of life in the world, both in the fields of economy, agriculture, education and so on. One of the impacts is on the field of education, the ministry of education issued a policy in the form of a circular on the learning process carried out by distance learning from home online, as well as the role of parents as the main supervisor during the learning process. Purpose: Thus the purpose of this writing is to find out how to establish the character education of learners during distance learning, because during this pandemic, children spend more time at home in order to be disconnected from the spread of the coronavirus. Design and methods: This research uses qualitative method with the type of literature study, as well as the reflection of researchers in the form of knowledge, insight and experience of researchers from the current situation. Results: In this study discussed that the formation of character education of learners can be formed by both parents as mentors during distance learning by habituating good behavior in order to become good human beings in adulthood under any circumstance